Perlindungan Hukum Bagi Suami Sebagai Korban Kejahatan Marital Rape Dalam Rumah Tangga - Sella Novianti; Aisyah Maharani Fajrin; Febbyolah; Nabilla Putrie V.S; Rizaldi; Enni Merita (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Violence often experienced by people living within a family is not limited to women and men, as a husband can also be victims of domestic violence (KDRT). Sexual violence experienced by men today is one of the kinds of crime that gets less public attention. This is because over the years, women have always been victims and perpetrators of sexual harassment, while men are perpetrats. This research uses normative jurisprudence, which is a type of descriptive research. The result will be that the marriage relationship must enhance both, complement each other, and there is a balance of rights and duties. Men also have the right to laws and regulations supported by law enforcement agencies and other agencies working together to protect victims of crime.